Classroom Interaction in the EFL Speaking Class in Junior High School - Kurniawan, Made Budi (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
The teaching and learning process is very dependent on the interactions that occur between teachers and students. The interaction occurs when the two subjects (teacher and student) speak. The purpose of this study is to analyze the types of interactions that were carried out during speaking class, teacher talk and student talk. This study uses a qualitative design with research subjects were English teachers and 35 students in grade 8 at SMP Negeri 5 Singaraja. The data were obtained using observation and using the Foreign Language Interaction (FLINT) system as data analysis. There were three current flows of analysis method namely: data reduction, data display, and conclusion/verification. The result of study reveal that there were seven types of classroom interaction. Those types of classroom interaction have the role to support the successful of the learning process. The most high percentage of teacher talk is teacher-whole class which the class almost done with the all interaction by the teacher to the students.